The 1981 Four Corners States Biennial Exhibition. - The Poenix Biennial, 1981 (Phoenix : Phoenix Art Museum, 1981)
Farnsworth, John ; Linderman, Earl ; Wagner, Ron ; Gasowski, Ron ; Davis, James G. ; Smith, Frank Anthony ; Gillingwater, Denis ; Jones, Dennis ; Goo, Ben ; Waid, Jim ; Birr, Marlene ; Rieke, Zachariah ; Newman, Margaret ; etc.
The 1981 Four Corners States Biennial Exhibition, Phoenix Art Museum, Phoenix, April 25 - May 24, 1981
boek